Гепатоцеллюлярный рак: иммуногистохимическая характеристика апоптоза и пролиферативной активности клеток - Туманский, В. А.; Зубко, М. Д.; Туманський, Валерій Олексійович; Зубко, Марія Дмитрівна; Tumanskiy, V. A.; Zubko, M. D. (My University, 2014)
З метою визначення апоптотичної і проліферативної активності клітин гепатоцелюлярної карциноми (ГЦК) в трепанобіоптатах печінки проведено імуногістохімічне дослідження рівня експресії р53, каспаз-3 і Кі-67 у 53 хворих гепатоцелюлярним раком. Встановлено, що в 62,26% спостережень в клітинах ГЦК виявлялася гіперекспресія ядерного білка р53, в 20,75% спостережень - високий рівень експресії цього протеїну і в 16,98% випадків - низький рівень експресії р53; середня площа р53-іммунопозітівних клітин становила 52,07±33,97. Одночасно в ГЦК переважав слабкий рівень цитоплазматичної експресії каспази-3 пухлинними клітинами, виявлених у 47,16% хворих, помірний рівень експресії каспази-3 клітинами ГЦК був встановлений у 26,42% пацієнтів, виражена експресія каспаз-3 клітинами ГЦК виявлена у 26, 42%; каспаза-3-іммунопозітивні клітини займали 48,21±27,66 % загальної площі ГЦК. Встановлено, що в ГЦК переважав помірний рівень експресії Ki-67, що спостерігався у 66,04% хворих, у 22,64% пацієнтів він був високим і у 11,32% хворих - низьким; при цьому Ki-67-іммупозітівние клітини займали 53,39±23,25% загальної площі пухлини. Таким чином, гіперекспресcія ядерного білка р53 в ГЦК асоціюється зі слабким і низьким рівнем апоптозу пухлинних клітин, а також переважно з помірним рівнем їх проліферації. Background. Hepatocellular carcinoma which takes about 85% of primary liver cancer, is the most aggressive and prognostically unfavorable tumor. Current information about the level of apoptosis and cell proliferative activity of HCC are contradictory. Objective. To determine the apoptotic and proliferative activity of hepatocellular carcinoma of the liver by the immunohistochemically level of p53, caspase-3 and Ki-67 expression. Methods. Trephine biopsies of 53 patients with hepatocellular carcinoma were studied. Results. It was found that in 62.26% of cases the hyperexpression of nuclear p53 protein in cells was detected, in 20.75% of cases - a high level of expression of this protein, and in 16.98% of cases - a low level of p53 expression. The average area of p53-immunopositive cells was 52,07±33,97%. Simultaneously, in 47.16% of hepatocellular carcinoma it was detected a weak level of cytoplasmic expression of caspase-3, in 26.42% of the patients moderate level of expression of caspase-3 by hepatocellular carcinoma cells was determined, pronounced expression of caspase- 3 was detected in hepatocellular carcinoma cells 26, 42%. Caspase-3-immunopositive cells occupied 48,21±27,66% of the total area of hepatocellular carcinoma. It is established that in the hepatocellular carcinoma prevailed moderate level of expression of Ki-67, which was observed in 66.04% of patients, in 22.64% it was high and in 11.32% of cases – it was low. Immupositive Ki-67 cells occupied 53,39±23,25% of the total area of the tumor. Conclusion. Hyperexpression of nuclear p53 protein in hepatocellular carcinoma was associated with weak and low level of apoptosis of tumor cells and moderate level of their proliferation.
Гепатоцелюлярний рак: імуногістохімічна характеристика апоптозу і проліферативної активності клітин.
Hepatocellular carcinoma: immunohistochemical characteristics of apoptosis and cell proliferation activity.
Keywords: гепатоцелюлярний рак; експресія; р53; каспаза-3; Кі-67; hepatocellular cancer; expression of p53; caspase-3